The Influence of Service Quality and Brand Image on Customer Satisfaction: Study on One of The Fast-Food Restaurants in Bandung - Kusuma, Alvina Faradila; Juhana, Dudung; Zulfikar, Vicky Achmad; Purana, R. Deni; Suswanto, Djadjat (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
This study sought to evaluate the influence of Service Quality and Brand Image on Customer Satisfaction at a fast-food restaurant in Bandung. This study utilizes a quantitative methodology with multiple linear regression techniques (path analysis) to investigate the relationships among variables. The research sample was obtained using the Slovin method, resulting in 84 participants from the restaurant's clientele. Data was collected using a Likert scale questionnaire to evaluate respondents' perceptions of service quality, brand image, and customer satisfaction. The data were analyzed using SPSS software version 23.0 to evaluate validity, reliability, and inter-variable correlations in this study.The results revealed that the average total Service Quality was 2.70, classifying it as